(untitled) (World Bulletin of Social Sciences, 2021)
Among the urgent and widely discussed problems at the present stage, a special place is occupied by the problem of improving education, improving its quality, achieving a high level of competitiveness in the modern labor market. This means that the education system is moving from a traditional focus solely on acquiring knowledge, skills and abilities more and more actively towards ensuring the broad competence of its graduates, from a knowledge paradigm to the creation of various options for educational and competence models that provide future specialists with the opportunity to freely navigate in a rapidly developing space. modern culture.